Sociobiology of caviomorph rodents : an integrative approach - Ebensperger, Luis A. (Luis Alberto); Hayes, Loren D. (Chichester, UK ; Hoboken, NJ : Wiley/Blackwell, 2016)
Fully integrative approach to the socibiology of caviomorph rodents -Brings together research on social systems with that on epigenetic, neurendocrine and developmental mechanisms of social behavior -Describes the social systems of many previously understudied caviomorph species, identifying the fitness costs and benefits of social living in current day populations as well as quantified evolutionary patterns or trends -Highlights potential parallels and differences with other animal models
4.4.2 Social deprivation effects on the emotional and social development of young guinea pigs4.5 Discussion and future research directions; 4.5 References; Chapter 5 Dispersal in caviomorph rodents; 5.1 Introduction; 5.2 What is dispersal?; 5.3 Studying dispersal: logistic challenges; 5.4 Dispersal in caviomorph rodents; 5.5 Understanding dispersal: adaptive explanations; 5.5.1 Why do individuals disperse?; 5.5.2 Why is dispersal male-biased?; 5.6 Understanding dispersal: proximate explanations; 5.7 Consequences of dispersal: social behavior; 5.8 Consequences of dispersal: genetic structure
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Caviomorpha; Rodents -- Behavior; NATURE / Animals / Mammals; SCIENCE / Life Sciences / Zoology / Mammals; Caviomorpha; Rodents -- Behavior; Electronic books; Electronic books; Electronic books